Humic acid induced indirect photolysis of polybrominated diphenyl ethers under visible light irradiation. Issue 3 (June 2022) - Yang, Meiying; Jin, Xueqing; Huang, Wenna; Shen, Qi; Sun, Chunyan
Abstract: Polybrominated diphenyl ethers (PBDEs), as typical persistent organic pollutants (POPs) have been world widely detected in environmental media and biological tissues. Compared with the extensive study on direct photolysis of PBDEs in the ultraviolet region (UV), indirect photodegradation of PBDEs under visible light triggered by the co-existing substances in the environment has been largely ignored. Herein, the indirect photolysis and debromination of organic brominated pollutants decabromodiphenyl ether (BDE209) induced by humic acid (HA) have achieved both in homogeneous and heterogeneous system under visible light irradiation. It shows a new transformation pathway of PBDEs in environment that plays an important role on their ultimate environmental fate. Different from direct photolysis of PBDEs in UV light, the indirect photolysis of PBDEs by HA under visible light irradiation experiences the electrons transfer from HA to PBDEs induced by a halogen-bond between HA and PBDEs. HA contributes to the activation of C-Br bond via formation of halogen bond, and promotes electron transfer under visible light irradiation, leading to meta- C-Br cleavage preferentially. To evaluate the effects of various functional groups in HA, eleven low-molecular-weight organic compounds (LMWOs) containing reactive oxygen terminal are selected to study the indirect photolysis of BDE209. Combined with the density functional theory (DFT) calculation results, it is shown that carboxyl group is proposed to be the key functional group capable of providing oxygen terminals to form halogen bonds. This work provides novel and valuable insights into the photolysis and debromination of PBDEs with co-existing HA in the environment under sunlight. Graphical Abstract: ga1 Highlights: The indirect visible light photolysis of BDE209 by HA is first realized. The activation of C-Br bond is due to the halogen-oxygen bond between BDE209 and HA. Carboxyl group in HA is proposed to be the key form halogen bonds with BDE209.